PERENCANAAN STRUKTUR ATAS GEDUNG HOTEL HIDAYAH PADANG PANJANG - Ivan Fikri Naldo; Surya Eka Priana; Febrimen Herista (Ensiklopedia Social Review, 2022)
The structural planning of the Hidayah Padang Panjang Hotel Building according to SNI 03-2847-2002 article 23.2.3, states that for areas with a moderate earthquake risk, a special or medium moment resisting frame system must be used, or an ordinary or special concrete structure wall system to carry the force. -forces caused by the earthquake. The stages of structural planning include analyzing the state and condition of the soil, designing the configuration of the building structure and its structural system, determining the loads acting on the structure, and finally making design drawings. Based on the results of this structural analysis, the reinforcement structure is obtained based on the author's analysis. The results obtained that the material used is steel fy = 420 Mpa and concrete quality fc' = 24.9 Mpa. For floor slab reinforcement, reinforcement is used for the x =Æ 10-150 direction while the y direction =Æ 10-150. Column design uses steel quality fy = 420 MPa and concrete quality fc' = 24.9 MPa with dimensions for column 1 60 x 30 cm using 16D-19 reinforcement. While the design of the beam using steel quality fy = 420 Mpa and concrete quality fc' = 24.9 Mpa with a main beam size of 60 x 30 cm. Keywords: earthquake load, superstructure, beam reinforcement, column reinforcement, plate reinforcement